Basileus Meets Imperator: Herod’s Evolving Honors to Augustus - Burrell, Barbara (Bulletin of ASOR, 2020)
This paper uses recent finds and reinterpretations (archaeological, epigraphic, and historical) to re-examine and place in a wider context Herod the Great’s actions towards honoring Augustus in his realm. As a king formerly allied with Antony, Herod needed to placate Augustus quickly after Actium. At first he showered his new overlord with service, money, and supplies, but it may have been in imitation of cities like Pergamon in Asia that he established a festival in Augustus’s honor in Jerusalem. We hear nothing of actual temples, however, until after Augustus granted Herod new territories; it was there, in non-Jewish areas, that Herod founded cities (which was what kings did), named them in honor of his sole superior, and built in them temples to Augustus and Roma, perhaps again on the model of Hellenic cities of Asia or Bithynia, or of Alexandria in Egypt. Herod did this not for the sake of Hellenization or Romanization, but to reify his relationship with Augustus before his kingdom and the world, enshrining him in the sole place in the hierarchy that a king could tolerate, and also, not incidentally, to show his own magnificence.